BUILDING RELATIONSHIPS VIA DATING APPS: TRUST AS THE FOUNDATION OF SELF-DISCLOSURE AMONG EMERGING ADULTS - Chaya Astara Clarine; Vania Ardelia (Psyche: Jurnal Psikologi, 2026)
Currently, many dating app users in Indonesia fall into the emerging adult age group. This study aims to examine the influence of trust on self-disclosure among emerging adults using dating apps. This study employs a quantitative research method with a cross-sectional survey design. In this study, 210 emerging adult users of dating apps were recruited using purposive sampling. The instruments used were a trust scale and a self-disclosure scale, both of which had been tested for validity and reliability. The data obtained from the questionnaire were then subjected to regression analysis after undergoing tests for normality and linearity. Results showed that trust significantly influenced self-disclosure among young dating apps users (F = 97.50; p < 0.05; R2 = 0.319), indicating that the trust variable (X) explains 31.9% of the variance in the self-disclosure variable (Y). These findings suggest that trust and self-disclosure are important in building relationships with partners met through dating apps. The results of this study can serve as a framework for understanding the development of trust and self-disclosure in the use of dating apps. Additionally, this research contributes to the literature on the interactions and communication of adults who use dating apps.